Urgensitas Tindakan Resiprokal dalam Pemahaman Love Language Pasangan; Upaya Menjaga Keharmonisan Rumah Tangga (Perspektif Hukum Islam) - Dwi Arini Zubaidah (Legitima : Jurnal Hukum Keluarga Islam, 2022)
The purpose an essential point of view, domestic life should be decorated with happiness and love that are sought and felt by husband and wife. However, according to the reality, the rift in the household is a signal that disharmony has taken root in it, so there needs to be a solution that is representative and solutionable. The type of research used by the author is normative legal research with a conceptual approach that collects library data in the form of research sector data on family disharmony, theories about the love language of couples and theories in the realm of Islamic law. The results of this study are love language is an act or expression of a husband and wife towards their partner which can grow their love. There are five love languages, namely affirmation words (sentences from partners), quality time (providing time by partners), receiving gifts (gifts by partners associated with certain moments), acts of service (service needs). from a partner) and physical touch (any physical expression of affection). Preventive efforts against household disharmony by applying the principle of reciprocal relations between husband and wife in Islamic law, namely mu'asyarah bil ma'ruf (doing good to each other) and taradhin minhuma (mutually willing to each other).